Library for the Digital Natives Generation: What to do? - Halim, Siana; Wulandari, Dian; Kasih, Demmy; -, Felecia; -, Inggrid (Universitas Airlangga, 2016)
Nowadays, people do not need to go to the library for searching knowledge or information. World has changed. We come to the new generation that so called as digital native generation. Information can be searched through the gadgets on hands which is connected to the internet. Then question comes, is the library still important? What should the library do? It is no wonder that most of the libraries have been decreasing its number of visitors as well as its number of books that out of the shells. This paper describes the characteristics of the digital native, people habit in learning and reading books.Â It also summarizes some discussions among the heads of the three university libraries in Surabaya, i.e, Intitut Teknologi Sepuluh (ITS) Nopember Surabaya, Petra Christian University (PCU), Surabaya Universities (Ubaya). The results of the discussion show that library has to be changed so that they can accommodate the needs of the digital native. It is not only the place for borrowing books, but also the place for doing discussion, watching videos and listening to audios, and of course the online materials must be provided to encounter the decreasing visitors.